Sino-Turkish Strategic Partnership: Prudent Hedging or Irreversible Shift?. (February 2013) - Kumar, Atul
The accelerated growth of Sino-Turkish relations indicates their increasing convergence on foreign, economic and security policies, despite several constraints. The deterioration of Turco-American relationship and frustrated Turkish ambitions of EU membership, coupled with a desire to diversify its arms acquisitions and balance its foreign policy, have led to the readjustments in its foreign and security policy. This realignment has resulted in closer Sino-Turkish partnership and emergence of the strategic cooperation. In China, a growing realisation has emerged in favour of Turkey's geo-strategic and geopolitical importance and its potential as a market for Chinese defence exports. Turkey as a client may impart much sought after international credibility to Chinese weapon manufacturers and a base in Turkey would enhance Chinese access to regional markets. Hence, China has increasingly courted Turkey and Chinese companies have increased their operations inside Turkey. In addition, there are significant convergences between both armed forces on issues of national security, separatism and terrorism. Consequently, strategic cooperation between China and Turkey has increased considerably in the last decade.